Openness doesn’t hurt : enforcing qualified machine-learning transparency for data protection through responsive regulation - Pereira, José Renato Laranjeira de (2022)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Direito, Programa de Pós-Graduação em Direito, 2022.